2013
DOI: 10.1099/vir.0.052837-0
|View full text |Cite
|
Sign up to set email alerts
|

Recent host-shifts in ranaviruses: signatures of positive selection in the viral genome

Abstract: Ranaviruses have been implicated in recent declines in global amphibian populations. Compared with the family Iridoviridae, to which the genus Ranavirus belongs, ranaviruses have a wide host range in that species/strains are known to infect fish, amphibians and reptiles, presumably due to recent host-switching events. We used eight sequenced ranavirus genomes and two selectiondetection methods (site based and branch based) to identify genes that exhibited signatures of positive selection, potentially due to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
29
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 67 publications
6
29
0
1
Order By: Relevance
“…Sequencing demonstrated that several ranaviruses (FV3, STIV) carry only a truncated version of the vIF-2α gene that lacks the amino-terminal binding domain for the protein kinase R and the central helical domains. All ranaviruses with truncated vIF-2α genes branched very closely to one another in the FV3-like group, which supports previous findings on sequence gain and loss during ranaviral evolution (Abrams et al 2013;Anke et al 2015). Thus, it is reasonable to infer that, based on the phylogenetic analysis, SGIV is more distantly related to an ISKNV-like megalocytivirus, which may be the result of an ISKNV-like megalocytivirus gaining and losing VP39 orthologs during its evolution.…”
Section: Discussionsupporting
confidence: 74%
“…Sequencing demonstrated that several ranaviruses (FV3, STIV) carry only a truncated version of the vIF-2α gene that lacks the amino-terminal binding domain for the protein kinase R and the central helical domains. All ranaviruses with truncated vIF-2α genes branched very closely to one another in the FV3-like group, which supports previous findings on sequence gain and loss during ranaviral evolution (Abrams et al 2013;Anke et al 2015). Thus, it is reasonable to infer that, based on the phylogenetic analysis, SGIV is more distantly related to an ISKNV-like megalocytivirus, which may be the result of an ISKNV-like megalocytivirus gaining and losing VP39 orthologs during its evolution.…”
Section: Discussionsupporting
confidence: 74%
“…Notably, the remarkable ability of RVs to cross species barriers of numerous ectothermic vertebrates, suggests that these pathogens possess potent immune evasion mechanisms [3]. Furthermore, although some ectothermic vertebrate species are highly susceptible to RVs, others are more resistant and may serve as asymptomatic carriers that disseminate infectious virus.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive comparisons of these important core genes has provided evidence for cross-species transmission in these iridoviruses, especially for the ranaviruses [68,69]. Moreover, some important genes encoding enzymes, structural proteins and immune-related proteins, such as the RGV 3β-hydroxysteroid dehydrogenase gene (RGV 3β-HSD) [70] and the RGV deoxyuridine triphosphatase gene (RGV dUTPase) [71], have been characterized and functionally analyzed.…”
Section: Important Core Genes and Their Functions In Iridovirusesmentioning
confidence: 99%